2020
DOI: 10.1093/jas/skaa224
|View full text |Cite
|
Sign up to set email alerts
|

Thermomechanical and enzyme-facilitated processing of soybean meal enhanced in vitro kinetics of protein digestion and protein and amino acid digestibility in weaned pigs

Abstract: Soybean meal (SBM) contains anti-nutritional factors (ANF) that may limit kinetics and total extent of protein digestion in pigs. This study evaluated effects of thermo-mechanical and enzyme-facilitated (TE) processing on in vitro kinetics of crude protein (CP) digestion and CP and amino acid (AA) digestibility in weaned pigs. Each batch of SBM (48% CP) was divided into 2 parts: non-processed SBM as control vs. thermo-mechanical and enzyme-facilitated processed soybean meal (TES) as experimental group. For dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…These authors also demonstrated that the differences in IVPD values were consistent with differences observed for standardized ileal digestible coefficients for crude protein, being 88.4% and 90.3% (p < .001) for the conventional and advanced processed soybean meal, as measured in an in vivo pig study (Nu et al, 2020). In the current study, the IV-SGPD% values for all the cooked potato samples were significantly different from the raw control (Table 3), with all methods being higher than the control.…”
Section: Department Ofsupporting
confidence: 69%
See 1 more Smart Citation
“…These authors also demonstrated that the differences in IVPD values were consistent with differences observed for standardized ileal digestible coefficients for crude protein, being 88.4% and 90.3% (p < .001) for the conventional and advanced processed soybean meal, as measured in an in vivo pig study (Nu et al, 2020). In the current study, the IV-SGPD% values for all the cooked potato samples were significantly different from the raw control (Table 3), with all methods being higher than the control.…”
Section: Department Ofsupporting
confidence: 69%
“…The use of the IV-SGDPD% method represents a step up in complexity in that, while still being a static method, it employs a two-stage digestion protocol (gastric and intestinal), with the addition of α-amylase. Nu et al (2020) used a similar method to compare the in vitro protein digestibility of conventional and thermomechanical and enzymefacilitated processed soybean meal for pigs and determined that the advanced processing methods used for soybean preparation yielded a product with higher IVPD (74.6% vs. 81.1% at 6 h total digestion).…”
Section: Department Ofmentioning
confidence: 99%
“…In addition, fractionation processes can generate novel high-protein DDGS fractions ( Cristobal et al, 2020 ) with enriched P content. Likewise, enzyme and extrusion technologies have generated highly digestible soy protein concentrates as novel feed ingredients for nursery pigs ( Ton Nu et al, 2020 ) to further expand the array of soy protein feedstuffs ( Yáñez et al, 2019 ). Finally, recycled coproducts (food waste) from the food industry might become important for the feeding of pigs ( Woyengo et al, 2015 ; Fondevila et al, 2021 ).…”
Section: Crops and Coproductsmentioning
confidence: 99%
“…As illustrated in Table 5 , studies have examined digestion kinetics of starch and protein, and fiber fermentation. Furthermore, quantitative information on differences in nutrient digestion or fermentation kinetics among different feedstuffs or purified sources were classified based on fast, slow, and resistant digestible nutrients [ 38 , 39 , 41 , 61 , 67 , 68 ]. Nevertheless, further research into the role of the synergistic effects of nutrient digestion is required because undigested nutrients may affect the digestion of other nutrients [ 18 ].…”
Section: In Vitro Nutrient Digestion Kinetics Of Feedstuffs For Pigsmentioning
confidence: 99%
“…The ANF may modulate the digestion and utilization of dietary protein and AA. Effects of thermomechanical and enzyme-facilitated processed SBM compared with non-processed SBM on in vitro kinetics of protein digestion and protein and AA digestibility in weaned pigs have previously been studied [ 39 ]. Processing reduced the ANF content (lectin, trypsin inhibitor activity, β-conglycinin, and glycinin) compared with non-processed SBM, and increased digested CP, tended to increase fast-digestible CP, and reduced slow and resistant CP compared with non-processed SBM.…”
Section: In Vitro Nutrient Digestion Kinetics Of Feedstuffs For Pigsmentioning
confidence: 99%